Blocking VCAM-1 ameliorates hypertensive cardiac remodeling by impeding macrophage infiltration - Qiu, Ze-Yang; Yu, Wei-Jia; Bai, Jie; Lin, Qiu-Yue (Frontiers in Pharmacology, 2022)
Cardiac remodeling is an important mechanism of heart failure, which frequently results from leukocyte infiltration. Vascular cellular adhesion molecule-1 (VCAM-1) plays a critical role in leukocyte adhesion and transmigration. However, the importance of VCAM-1 in the development of angiotensin II (Ang II)-induced cardiac remodeling remains unclear. Wild-type (WT) mice were infused with Ang II (1000 ng/kg/min) for 14 days and simultaneously treated with VCAM-1 neutralizing antibody (0.1 or 0.2 mg) or IgG control. Systolic blood pressure (SBP) and cardiac function were detected by a tail-cuff and echocardiography. Cardiac remodeling was evaluated by histological staining. Adhesion and migration of bone marrow macrophages (BMMs) were evaluated in vitro. Our results indicated that VCAM-1 levels were increased in the serum of patients with heart failure (HF) and the hearts of Ang II-infused mice. Furthermore, Ang II-caused hypertension, cardiac dysfunction, hypertrophy, fibrosis, infiltration of VLA-4+ BMMs and oxidative stress were dose-dependently attenuated in mice administered VCAM-1 neutralizing antibody. In addition, blocking VCAM-1 markedly alleviated Ang II-induced BMMs adhesion and migration, therefore inhibited cardiomyocyte hypertrophy and fibroblast activation. In conclusion, the data reveal that blocking VCAM-1 ameliorates hypertensive cardiac remodeling by impeding VLA-4+ macrophage infiltration. Selective blockage of VCAM-1 may be a novel therapeutic strategy for hypertensive cardiac diseases.